Thermal analysis for the HTS stator consisting of HTS armature windings and an iron core for a 2.5 kW HTS generator. (17th March 2016) - Song, P; Qu, T-M; Lai, L-F; Wu, M-S; Yu, X-Y; Han, Z
Abstract: Most present demonstrations of high-temperature superconducting (HTS) synchronous motors/generators are partially superconducting, only installing HTS coils on the rotor as excitation windings. The possible applicability of HTS armature windings is an interesting research topic because these windings can certainly increase the power density attributed to a potentially high armature loading capacity. In this study, we analysed the thermal behaviours of a developed 2.5 kW–300 rpm synchronous generator prototype that consists of an HTS stator with Bi-2223–Ag armature windings on an iron core and a permanent magnet (PM) rotor. The entire HTS stator, including the iron core, is cooled with liquid nitrogen through conduction cooling. The rated frequency is set at 10 Hz to reduce AC loss. The properties of the HTS windings and the iron core are characterized, and the temperatures in the HTS stator under different operation conditions are measured. The estimated iron loss is 11.5 W under operation in 10 Hz at liquid nitrogen temperature. Conduction cooling through the silicon iron core is sufficient to cool the iron core and to compensate for the temperature increment caused by iron loss. The stable running capacity is limited to 1.6 kW when the armature current is 12.6 A (effective values) due to the increasing temperature in the slots as a result of the AC loss in the HTS coils. The thermal contact between the HTS coils and the cooling media should be improved in the future to take away the heat generated by AC loss.